Direct Amidation of ethyl p-methoxycinnamate to Produce N,N-bis-(2-hydroxyethyl)-p-methoxycinnamamide - Ismiarni Komala; Supandi Supandi; Muhammad Mirza Hardiansyah (Jurnal Kimia Valensi, 2018)
Ethyl p-methoxycinnamate (EPMC) (1) is found as a major natural ester in the rhizome of Kaempferia galanga (kencur) and has been known to have various pharmacological activities. The previous study has reported the synthesis of N,N-bis-(2-hydroxyethyl)-p-methoxycinnamamide (2) by using microwave-assisted direct amidation of EPMC (1) with diethanolamine. In this research, we attempt to synthesize of 2 by using a conventional direct amidation of EPMC (1) with diethanolamine. The reaction was conducted without adding any coupling reagents or catalyst. Structure of the synthetic product was determined by using analysis of GC-MS, IR, and 1H-NMR spectroscopic data and then compared to the previously reported.DOI:http://dx.doi.org/10.15408/jkv.v4i1.7300